The Future of copyright in a digital environment : proceedings of the Royal Academy Colloquium organized by the Royal Netherlands Academy of Sciences (KNAW) and the Institute for Information Law, (Amsterdam, 6-7 July 1995) /: proceedings of the Royal Academy Colloquium organized by the Royal Netherlands Academy of Sciences (KNAW) and the Institute for Information Law, (Amsterdam, 6-7 July 1995). (1996) - Unknown
No abstract available